Clinical and genetic analysis of atypical parathyroid adenoma compared with parathyroid carcinoma and benign lesions in a Chinese cohort - Chen, Yingyu; Song, An; Nie, Min; Jiang, Yan; Li, Mei; Xia, Weibo; Wang, Ou; Xing, Xiaoping (Frontiers in Endocrinology, 2023)
Context: The malignant potential and molecular signature of atypical parathyroid adenoma (APA) remain elusive. Data from Asia are still lacking. Design and Setting: This was a retrospective study on a large APA cohort in a single center from mainland China. Methods. A total of 320 patients with primary hyperparathyroidism (PHPT), containing 79 APA, 79 Parathyroid cancer (PC) and 162 benign lesions cases, were enrolled after surgery for collection of clinical data and genetic analysis. Results: APA patients showed earlier mean onset age than benign group (46.9±17.1 vs. 52.0±14.3 yrs). Less bone involvement and gastrointestinal symptoms were presented in APA compared to PC (35.4% vs. 62.0%, and 17.7% vs. 41.8%), while more urolithiasis was seen in APA than in benign lesions (57.0% vs. 29.6%). The APA group had moderate hypercalcemia (mean 3.02±0.44mmol/L) with elevated serum PTH (median 593.0pg/ml) and proportion of hypercalcemic crisis as 22.8%, all higher than those of benign lesions but lower than those of PC group. The recurrence/no remission rate of the APA group was significantly lower than that of the PC and similar to the benign group (5.1% vs. 31.6% vs. 3.1%). Germline CDC73 mutation was the most common molecular abnormality in both PC and APA subjects. APA patients with nonsynonymous germline variants showed earlier onset age (28.5±16.9 vs. 48.1±17.7 yrs) and more cases developing no remission/recurrence (25.0% vs. 0.0%). Conclusions: Patients with APA presented clinical and biochemical characteristics much less severe than PC and resembling the benign neoplasms, with a relatively good prognosis. Germline gene variations were associated with earlier onset and probably more recurrence of PHPT in APA.